Effects of pre- and post-natal exposure to bisphenol A on the stress system. (1st April 2016) - Kitraki, E.; Nalvarte, I.; Alavian-Ghavanini, A.; Rüegg, J.
ABSTRACT: Evidence is accumulating that developmental exposure to Bisphenol A (BPA), an abundant endocrine disrupting chemical (EDC), affects neurodevelopment and later brain function, including cognitive performance, social and affective behaviors. However, an impact of BPA exposure on the stress system regulators has only recently come into focus. This mini-review aims to summarize and discuss the available findings from animal studies regarding BPA effects on the stress system and the hypothalamic-pituitary- adrenal (HPA) axis in particular. It appears that perinatal exposure of rodents to low doses of BPA, around the human tolerable daily intake, can modify the levels, expression and epigenetic patterning of key stress mediators at later-life stages in a sex-specific way. These observations provide evidence that developmental exposure to one of the most highly produced chemicals today may contribute to the regulation of the stress axis. Given the importance of the HPA axis in coordination of the organisms' global homeostasis and its implications in stress-related disorders, further studies are needed to delineate the underling mechanisms of these BPA actions.